Analysis of the Deformation Characteristics and Formation Mechanism of Reservoir Landslides under Rainfall Conditions - DOU Sijun; XU Xingqian; LI Jiguo; LING Huikun; ZHOU Shasha (Renmin Zhujiang)
Hexi reservoir landslide is located in Tianyuan Town,Changning County,Baoshan City,Yunnan Province.There are obvious tensile cracks,fault,bank slope retaining wall and cut-off ditch crack deformation at its rear edge,which bring a serious threat to the safety of spillways and dam body.Based on the basic morphological features and geological environment conditions of the landslide,combined with the geological survey data,this paper analyzes the deformation characteristics and induced factors of the landslide and judges the landslide as a large-scale thick-layer traction-pushing bedding landslide,simulates the change of slope pore water pressure and safety coefficient under the conditions of different rainfall intensity and reservoir water level change by Geo-Studio numerical software,and analyzes & evaluates its stability.The results show that:Under continuous rainfall,the reservoir water level rises,the front edge of the slope body softens,the pressure of pore water in the slope body increases,the natural discharge effect produces,and the sliding force increases,which aggravate the deformation,failure and destabilization of slope body.In the process of the sudden drop of reservoir water level,the backpressure effect of the reservoir water is weakened,and the water penetration of the pre-slope body produces the dynamic water pressure,which is more likely to lead to the occurrence of such landslides.The steep slope terrain and bedding structure of downward rock formation in the landslide area create favorable conditions for the development of the landslide,and thecontinuous rainfall is the main factor of the landslide.The joint cutting slope and backpressure anti-slip pile is an effective means to prevent and control the landslide.The results can serve as theoretical reference for the analysis,judgment and timely prevention of similar landslides in daily operation and management of reservoir.